The Effect of Two Picture Game towards Students’ Speaking Anxiety - Muh. Mahrup Zainuddin Sabri (Universitas Pendidikan Mandalika, 2018)
This research is aimed to find out the effect of Two Picture Game Towards Students’ speaking Anxiety at SMAN 1 Jerowaru. The research was experimental research and the research design that was used quasi experimental, control and experimental group design. The population of the study was the IPS 1 and IPS 2 students of SMAN 1 Jerowaru which consisted of two classes. Two classes were chosen as the samples, those were IPS 1 as experimental class, and IPS 2 as control class. They were chosen by using sampling technique. Experimental class was treated by using two picture game, and control class was treated by slowly reveal. The data of the research were primarily gathered from post test and questionnaire, where the result of mean scores of an experimental class, was higher than the result of mean scores of control group. Then, in analyzing the data of the research the researcher used SPSS. Based on the analysis of the data above, it was found that t-test (to) score was 8.271 with the degree of freedom (df) = 20 and t-table (tt) was 000 at the significant level =0.05 It was showed that t-test is lower than t-table, in can be concluded that two picture game was not effective for students’ anxiety in speaking at SMAN 1 Jerowaru.